Dynamic adjustment neural network-based cooperative control for vehicle platoons with state constraints - Wang, Ping; Gao, Min; Li, Junyu; Zhang, Anguo (Zielona Góra: Uniwersytet Zielonogórski)
This paper addresses the challenge of managing state constraints in vehicle platoons, including maintaining safe distances and aligning velocities, which are key factors that contribute to performance degradation in platoon control. Traditional platoon control strategies, which rely on a constant time-headway policy, often lead to deteriorated performance and even instability, primarily during dynamic traffic conditions involving vehicle acceleration and deceleration.
Keywords: vehicle platoon; dynamic adjustment neural network (DANN); cooperative control; state constraint